Kajian Systematic Literature Review: Urgensi CS Unplugged dalam Meningkatkan Kemampuan Computational Thinking dan Logical Thinking Siswa - M. Daffa Al-Qory; Agung Arya Anggara; Eka Fitrajaya Rahman; Jajang Kusnendar (Journal of Creative Student Research, 2026)
Rapid technological developments have changed the way humans behave and interact, enabling them to adapt to various digitalized sectors of life. If humans fail to adapt to these developments, they will be left behind and uncompetitive due to the various challenges of this era. To survive the digital era, Computational Thinking (CT) and Logical Thinking (LT) are essential skills. These skills can be acquired through the educational process in schools, but schools in Indonesia face infrastructure constraints. Therefore, the Computer Science Unplugged (CSU) model can be an alternative to hone these two skills. This study aims to analyze and compare the results of previous studies regarding the effect of Computer Science Unplugged on Computational Thinking and Logical Thinking skills. The research method used in this study is a Systematic Literature Review with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method. The results of this study prove that CSU has a positive impact on computational thinking skills and logical thinking skills. Research on the effect of CSU on CT tends to be more numerous than the effect of CSU on LT. CSU research on CT has involved various levels of education, but research on the influence of CSU on LT is still limited to early childhood students. Therefore, there is still room for research on the influence of CSU on LT to obtain more comprehensive results.